Implementasi Model Kepemimpinan Situasional Kepala Sekolah di Lembaga Pendidikan Islam: Analisis Skema, Capaian dan Hambatan - Zukhruf, Wahid Muhammad; Azani, Mohammad Zakki (Fitrah: Journal of Islamic Education, 2023)
Determining the right leadership model by the principal will lead the school to the development of quality and service. The purpose of this study was to review the practice of the situational leadership model of the principal at SMP Daarul Quran Surakarta. The research method used is phenomenology-based qualitative with data collection techniques, namely observation, interviews, and documentation. Data analysis techniques through the stages of data reduction, data exposure and conclusions. The results of the study explain that the situational leadership model of the principal is applied with four schemes, namely: 1) telling, namely the establishment of one-way contact carried out by a superior, namely the principal to his subordinates / partners regarding notification of the details of the division of tasks; 2) selling, namely the existence of two-way contact carried out by a superior, namely the principal to his subordinates / partners regarding the division of tasks; 3) participating, namely the principal includes subordinates / partners in making decrees; 4) Delegating, namely the principal delegates authority to subordinates who have sufficient competence to complete certain tasks. The applied situational leadership is successful in improving the quality of education, although there are some obstacles, namely the motivation of subordinates to follow orders is still low, understanding of leadership is still not optimal.